The Role of Perceived Organizational Support in Mental Health of Healthcare Workers During the COVID-19 Pandemic: A Cross-Sectional Study - Chatzittofis, Andreas; Constantinidou, Anastasia; Artemiadis, Artemios; Michailidou, Kyriaki; Karanikola, Maria N. K. (Frontiers in Psychiatry, 2021)
Background: Data support the link between the coronavirus disease 2019 (COVID-19) pandemic and mental distress in healthcare workers (HCWs). Although previous studies have documented the association between organizational policies and employees’ psychological and mental status, there is still scant evidence regarding the effect of perceived organizational support (POS) on mental distress in HCWs during the pandemic. Aims: The present study aimed to assess the association between POS and mental distress in HCWs during the COVID-19 pandemic. The role of POS in stress, depressive and trauma symptoms in HCWs was investigated. Methods: This was an online cross-sectional study in 424 HCWs. Data were collected during the first wave of the pandemic, and included demographics, a 7-item questionnaire assessing POS, the “Patient Health Questionnaire” assessing depressive symptoms, the “Impact of Events Scale Revised”, measuring post-traumatic stress disorder (PTSD) symptoms and the “Perceived Stress Scale” assessing perceived stress. Results: The mean POS score was 3.33 [standard deviation:1.85; range 0-7]. Younger (p<0.001), less experienced (p<0.001), female (p=0.002), and non-physician HCWs (p=0.031) were more likely to report lower self-perceived organizational support than older, male, more experienced physicians. Self-perceived organizational support was significantly and negatively associated with and self-assessed intensity of stress, depressive and traumatic symptoms, after adjusting for putative confounders (p<0.001). Discussion: Self-perceived organizational support was significantly associated with HCWs’ self-assessed mental status during the pandemic. Organizational support and mental distress should be addressed simultaneously in HCWs during the COVID-19 pandemic to increase resilience among them.